Transcript Level Alterations Reflect Gene Dosage Effects Across Multiple Tissues in a Mouse Model of Down Syndrome - Kahlem, Pascal; Sultan, Marc; Herwig, Ralf; Steinfath, Matthias; Balzereit, Daniela; Eppens, Barbara; Saran, Nidhi G.; Pletcher, Mathew T.; South, Sarah T.; Stetten, Gail; Lehrach, Hans; Reeves, Roger H.; et al. (Genome Research, 2004)
Human trisomy 21, which results in Down syndrome (DS), is one of the most complicated congenital genetic anomalies compatible with life, yet little is known about the molecular basis of DS. It is generally accepted that chromosome 21 (Chr21) transcripts are overexpressed by about 50% in cells with an extra copy of this chromosome. However, this assumption is difficult to test in humans due to limited access to tissues, and direct support for this idea is available for only a few Chr21 genes or in a limited number of tissues. The Ts65Dn mouse is widely used as a model for studies of DS because it is at dosage imbalance for the orthologs of about half of the 284 Chr21 genes. Ts65Dn mice have several features that directly parallel developmental anomalies of DS. Here we compared the expression of 136 mouse orthologs of Chr21 genes in nine tissues of the trisomic and euploid mice. Nearly all of the 77 genes which are at dosage imbalance in Ts65Dn showed increased transcript levels in the tested tissues, providing direct support for a simple model of increased transcription proportional to the gene copy number. However, several genes escaped this rule, suggesting that they may be controlled by additional tissue-specific regulatory mechanisms revealed in the trisomic situation.